The Effect of Inventory Turnover on Return on Investment (ROI) in Pg. Rajawali II Cirebon - Ade Sobariah Hasanah (Return : Study of Management, Economic and Bussines, 2022)
Background: One of the main elements of working capital in a company is inventory turnover. Inventory is an asset that will continue to rotate and change continuously. A company must pay attention to this inventory turnover because it will indirectly have an impact on the development of the company. Aim: This study aims to determine the effect of inventory turnover on Return On Investment in PG. Rajawali II Cirebon. Method: The method used is the descriptive verification method. The population used in this study is inventory turnover data and Return On Investment (ROI) data from 2015 to 2020, the research sample is inventory turnover data and PG Return On Investment (ROI) data. Rajawali II Cirebon for the last six years (2015–2020) taken by purposive sampling technique. Findings: The results of the simple linear regression test obtained the equation = 21.215 + 0.303 X; This means that every increase in inventory turnover so far has increased the number of returns on Investments. From the results of the correlation test, the value of r = 0.868 means that the amount of inventory turnover has a very strong relationship with Return on Investment. The results of the determination test show that Return on Investment is influenced by inventory turnover of 75.30%, while the remaining 24.70% is influenced by other factors not examined. Based on the results of hypothesis testing using the t-test, the account value is 3,495, and stable at a = 0.05 and DK = 4 is 2.132; which means Ho is rejected or Ha is accepted. This means that inventory turnover has a positive and significant effect on the return on investment in PG. Rajawali II Cirebon